1999
DOI: 10.1375/bech.16.4.259
|View full text |Cite
|
Sign up to set email alerts
|

Assertive Community Treatment for Persons with Severe Mental Disorders: A Controlled Treatment Outcome Study

Abstract: The present study evaluated the efficacy of an Assertive Community Treatment (ACT) program for the seriously mentally ill. Outcomes of the program were assessed at baseline and 12-month follow-up and were compared with that of a control group, which received standard community care. Thirty-six subjects with serious mental disorders participated in the study. Dependent measures included number of hospital admissions and hospital bed days per year, life skills, quality of life, and psychiatric symptoms. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…As found in other studies (e.g. Clarke et al, 2000;Hamernik & Pakenham, 1999), both groups of participants (i.e. those receiving intensive case management and those receiving regular case management) demonstrated gains in a number of areas.…”
Section: Discussionsupporting
confidence: 82%
“…As found in other studies (e.g. Clarke et al, 2000;Hamernik & Pakenham, 1999), both groups of participants (i.e. those receiving intensive case management and those receiving regular case management) demonstrated gains in a number of areas.…”
Section: Discussionsupporting
confidence: 82%
“…[8][9][10][11][12][13][14][15][16][17][18] In turn, individuals assigned to the ACT condition used fewer emergency services and more outpatient services, including financial and housing assistance, relative to individuals in the control conditions. 13,14,16,19,23 A few studies also found that individuals assigned to the ACT condition reported decreased symptomatology, 17,20,22,24,25 increased medication adherence, 10,17 more contact with the treatment team, 23,26 more days in stable community housing, 7,12,13,17,19,21,25 and greater satisfaction with treatment among patients and their family members relative to the control condition.…”
Section: Port Psychosocial Treatment Recommendationsmentioning
confidence: 99%
“…Randomized trials with adults demonstrate that intensive case management and ACT are more effective than treatment as usual in reducing inpatient hospital care, improving housing stability, and are particularly useful for patients at high risk for treatment noncompliance and relapse (for reviews, see Essock, Drake, & Burns, 1998;Lehman et al, 1998a;Scott & Dixon, 1995). More modest effects have been reported for clinical, social, and quality of life outcomes (Hamernik & Pakenham, 1999;Mueser, Bond, Drake, & Resnick, 1998).…”
Section: B Treatment During Stabilization and Maintenance Phasesmentioning
confidence: 99%
“…Despite the promise of ACT for the treatment of adult schizophrenia, and the inclusion of older adolescents in some of the randomized trials (e.g., Hamernik & Pakenham, 1999), our review revealed no randomized controlled trials of this approach for youth suffering from schizophrenia. There is, however, a promising literature on treatment and service delivery strategies for youth with severe emotional disturbance and mental health crises that is directly applicable to youth with schizophrenia.…”
mentioning
confidence: 95%